Peran Badan Nasional Penanggulangan Terorisme (BNPT) dalam Upaya Penanggulangan Kelompok Kriminal Bersenjata (KKB) sebagai Kejahatan Terorisme (Studi di Badan Nasional Penanggulangan Terorisme) - Bellynda Shafira Aryeno; Teguh Suratman; Riski Febria Nurita (University of Merdeka Malang, 2022)
This riset discusses the role of the National Agency for Combating Terrorism, especially in the effort to overcome the Armed Criminal Group (KKB) in Papua as a crime of terrorism. Terrorist activities in Indonesia have threatened and claimed many victims. One of the actions carried out by the KKB in Papua. At first, this group labeled themselves as the Free Papua Organization. The OPM is a separatist group whose goal is to separate themselves from the Republic of Indonesia. The Indonesian government has agreed to categorize the KKB in Papua as a terrorism group based on Law Number 15 of 2018 concerning the Eradication of Criminal Acts of Terrorism. So far, KKB has only been categorized as a criminal group, where the way it is handled is different from that of a terrorist group. The purpose of this study was to determine the countermeasures carried out by BNPT in dealing with KKB in Papua as a crime of terrorism and also to find out the obstacles faced by BNPT in efforts to overcome KKB as a crime of terrorism. The type of research in this thesis is using empirical legal research or also known as juridical-sociological legal research. This study uses empirical facts taken from human behavior, both verbal behavior obtained from interviews and real ones through direct observation. The results of this thesis research are, BNPT in an effort to overcome KKB as a crime of terrorism has two approaches, namely a soft approach and a hard approach. In terms of the soft approach, BNPT has 3 programs in its implementation, namely the deradicalization program, counter radicalization, and also national preparedness. After that the hard approach.